Modified Karydakis procedure for uncomplicated pilonidal sinus - George, Thomas; Mathew, Joe (International Surgery Journal, 2020)
Background: Pilonidal sinus disease is a chronic infection of the natal cleft commonly affecting young adults. Out of the standard operative techniques, the Karydakis procedure is a relatively simple procedure associated with low rates of wound complications and recurrence. In this study we present a modified version of the Karydakis procedure to treat less extensive disease, which enables better skin closure without cavitation and tension. Methods: Patients with uncomplicated pilonidal sinus who presented to our centre during the period from April 2015 to March 2019 were prospectively enrolled. Patients with recurrent or complex sinus disease were excluded. In those enrolled, our modified Karydakis procedure was performed. In this method, after excision a flap of skin and subcutaneous tissue was raised to one side and sutured across the midline by advancement in layers. Results: 34 patients underwent our modified Karydakis procedure. 91% (31/34) of patients had uncomplicated recovery and could return to work after two weeks. There were minimal post-operative complications, in the form of erythema around the wound (8.8%), wound discharge (5.9%), seroma (5.9%) and infection (2.9%). No patient developed wound dehiscence or flap necrosis. There were excellent cosmetic results and no recurrence at one year post-surgery. Conclusions: Our modification of the Karydakis procedure is a simple and effective surgery for the management of uncomplicated pilonidal sinus disease which achieves good results.